Be Sweet to Babies: Consumer Evaluation of a Parent-Targeted Video Aimed at Improving Pain Management Strategies in Newborn Infants Undergoing Painful Procedures. (24th February 2023) - Bujalka, Helena; Cruz, Melinda; Ingate, Vivien; Cheong, Jeanie; Duffy, Natalie; Eeles, Abbey; Spence, Kaye; Spittle, Alicia; Sweet, Linda; Saracino, Amy Tagliante; Harrison, Denise
Abstract : Background: Evidence for analgesic effects of parent-led pain management strategies during painful procedures in newborn infants exists; however, such strategies are inconsistently used in practice. A publicly available parent-targeted video demonstrates breastfeeding, skin-to-skin care, and sucrose during painful procedures. Australian parents' use and knowledge of this video and these strategies was unknown. Purpose: To determine parents' use of pain management strategies, and perceived acceptability and usefulness of the parent-targeted video. Methods: A cross-sectional, online, anonymous survey with embedded video. Participants were recruited via social media channels of the Miracle Babies Foundation, an Australian parent support network. Target participants were parents or family members of infants currently or previously hospitalized in neonatal special and/or intensive care nurseries, or high dependency units. Results: A total of 162 of 189 respondents provided sufficient data for analysis; all identified as mothers. Only 6 (4%) had previously seen the video; however, nearly all rated it as potentially useful and helpful (n = 124, 82%). Although most reported that sucrose had been used (n = 112, 84%), fewer reported having used skin-to-skin care (n = 50, 37%), or breastfeeding (n = 33, 25%). Most intended to advocate for skin-to-skin care (n = 108, 88%) or breastfeeding (n = 100, 81%) in future procedures. Perceived barriers to utilizing strategies included lack of information-sharing and organizational practices that excluded parent involvement. Implications for Practice and Research: The video may be valuable in supporting mothers to advocate for their involvement during painful procedures in preterm and sick hospitalized infants. Further research is recommended to explore coordinated strategies targeting parents and healthcare professionals to overcome barriers to implementing parent-led infant pain management strategies.